Pengaruh Pemanfaatan Dana Bantuan Operasional Kesehatan terhadap Upaya Kesehatan Anak melalui Posyandu di Indonesia Berdasarkan Data IFLS Tahun 2014 - Nia Priyatiningsih; Atik Nurwahyuni (Media Kesehatan Masyarakat Indonesia, 2019)
Health Operational Aid Fund (BOK) is an effort of the Indonesian government to reduce mortality ofnewborns and toddlers, where in 2017 mortality rate of newborns reached 15 per 1000 live births and 32 per1000 live births for toddlers. BOK funds are used as operational costs for health workers/cadres in carrying outpromotional and preventive activities outside the building. This study aims to explain the effect of BOK funds onchild health efforts through on Integrated Health Center (IHC). This study used a secondary data study of 2014IFLS, with a cross-sectional study design and logit econometric model approach. Respondents in this study wasparents who have children aged 0-59 months, number of respondents was 4,417. Data processing used the STATAapplication. Results of study showed that children who were brought to IHC were significantly associated withp-value <0.1 on maternal education status, economic status and BOK Fund. Educational status has a p-valueof 0.087, economic status has a p-value of 0.019, and BOK funds have a p-value of 0.0001. BOK funds do notdirectly affect children’s health, but the utilization of BOK fund by health workers/cadres can provide awarenessof mothers who have toddlers to maintain children’s health through on IHC.